Highly efficient production of rabies virus glycoprotein G ectodomain in Sf9 insect cells - Targovnik, Alexandra Marisa; Ferrari, Alejandro; Mc Callum, Gregorio Juan; Arregui, Mariana Bernadett; Smith, Ignacio; Bracco, Lautaro Fidel; Alfonso, Victoria; Lopez, Maria Gabriela; Martínez‑Solís, María; Herrero, Salvador; Miranda, Maria Victoria (Springer, 2020)
In the present study, we developed a complete process to produce in insect cells a high amount of the ectodomain of rabies virus glycoprotein G (GE) as suitable antigen for detecting anti-rabies antibodies. Using the baculovirus expression vector system in Sf9 insect cells combined with a novel chimeric promoter (polh-pSeL), the expression level reached a yield of 4.1 ± 0.3 mg/L culture, which was significantly higher than that achieved with the standard polh promoter alone. The protein was recovered from the cell lysates and easily purified in only one step by metal ion affinity chromatography, with a yield of 95% and a purity of 87%. Finally, GE was successfully used in an assay to detect specific antibodies in serum samples derived from rabies-vaccinated animals. The efficient strategy developed in this work is an interesting method to produce high amounts of this glycoprotein.